Reducing Water Availability Impacts the Development of the Arbuscular Mycorrhizal Fungus Rhizophagus irregularis MUCL 41833 and Its Ability to Take Up and Transport Phosphorus Under in Vitro Conditions - Le Pioufle, Olivia; Declerck, Stéphane (Frontiers in Microbiology, 2018)
Climate change scenarios predict a higher variability in rainfall and an increased risk of water deficits during summers for the coming decades. For this reason, arbuscular mycorrhizal fungi (AMF) and their mitigating effects on drought stress in plants are increasingly considered in crop management. However, the impact of a decrease in water availability on the development of AMF and their ability to take up and transport inorganic phosphorus (Pi) to their hosts remain poorly explored. Here, Medicago truncatula plantlets were grown in association with Rhizophagus irregularis MUCL 41833 in bi-compartmented Petri plates. The system consisted in associating the plant and AMF in a root compartment (RC), allowing only the hyphae to extend in a root-free hyphal compartment (HC). Water availability in the HC was then lowered by increasing the concentration of polyethylene glycol-8000 (PEG 8000) from 0 to 10, 25 and 50 g L-1 (corresponding to a slight decrease in water potential of - 0,024, -0,025, -0,030 and -0,056 Mpa, respectively). Hyphal growth, spore production and germination were severely impaired at the lowest water availability. The dynamics of Pi uptake by the AMF was also impacted, although total Pi uptake evaluated after 24 h stayed unchanged. The percentage of metabolically-active extraradical hyphae remained above 70%. Finally, at the lowest water availability, a higher P concentration was observed in the shoots of M. truncatula. At reduced water availability, the extraradical mycelium development was impacted, potentially limiting its capacity to explore a higher volume of soil. Pi uptake was slowed down but not prevented. The sensitivity of R. irregularis MUCL 41833 to a, even small, decrease in water availability contrasted with several studies reporting tolerance of AMF to drought. This suggests a species or strain-dependent effect and support the necessity to compare the impact of water availability on morpho-anatomy, nutrient uptake and transport capacities of other, potentially more drought-tolerant (e.g. isolated from dry environments) AMF.